KEDUDUKAN ADVOKAT DALAM PASAL 5 UNDANG-UNDANG NOMOR 18 TAHUN 2003 TENTANG ADVOKAT PERSPEKTIF HUKUM - Umam, Adib Khoirul (Jurisdictie: Jurnal Hukum dan Syariah, 2014)
This study aims to determine how Islam views which in this case is limited only four schools of opinion about the position of an advocate as law enforcement. In Islam indeed advocates known as providers of legal bantuah namely Hakam, mufti and mashalih alaih that functions similar to advokat.Penelitian function is called normative research with descriptive methods comparative analysis between positive law and Islamic law, namely Law No. 18 2003 and scholarly opinion four schools as primary data. Secondary data were taken from books or books that explain the legal theory of primary data. Article 5 of Law No. 18 of 2003 on lawyers has been explained that the position of advocate parallel with other law enforcement such as judges, prosecutors and police. But in fact appear black advocates not to enforce the law but instead became mafias that sell traded equity law. For it will be studied how exactly Islam's view of the position of Advocates with the formulation of the problem sebegai follows, first how the views of Islamic law for the position of advocate in Article 5 of Law No. 18 of 2003 on advocates, who both like where the relevance of Islam's view of the position of advocate in enforcement law in Indonesia. From research conducted authors argue for their refisi against the law number 18 of 2003 on advocates. alignment between advocates and other law enforcement must be followed by the high quality of an advocate and supervision of the performance of lawyers in order to minimize the occurrence of fraud in practice in providing legal aid.Penelitian ini bertujuan untuk mengetahui bagaimana pandangan Islam yang dalam hal ini hanya dibatasi pendapat empat madzhab tentang kedudukan advokat sebagai penegak hukum. Dalam Islam memang advokat dikenal sebagai lembaga pemberi bantuah hukum yaitu hakam, mufti dan mashalih alaih yang secara fungsi hampir sama dengan fungsi advokat. Penelitian ini disebut penelitian normatif dengan metode deskriptif analisis perbandingan antara hukum positif dan hukum Islam, yaitu undang-undang nomor 18 tahun 2003 dan pendapat ulama empat madzhab sebagai data primer. Data sekunder diambil dari kitab-kitab atau buku-buku teori hukum yang menjelaskan tentang data primer. Dari penelitian yang dilakukan penulis berpendapat perlunya adanya refisi terhadap undang-undang nomor 18 tahun 2003 tentang advokat. kesejajaran antara advokat dan penegak hukum lainya harus diikuti dengan tingginya kualitas seorang advokat dan pengawasan terhadap kinerja advokat agar bisa meminimalisir terjadinya penyelewengan dalam praktiknya dalam memberi bantuan hukum.